The Russian anesthesiology and resuscitation in 2019–2020 - Yu. S. Polushin (Вестник анестезиологии и реаниматологии, 2020)
The editorial considers the results and development trends of anesthesiology and resuscitation in this country after the 2nd Congress On Topical Issues of Critical Care Medicine which was held last year. Special attention is paid to the practical implementation of the concepts of enhanced recovery of the patient and perioperative medicine as well as acute kidney injury. It is noted that a change in the conceptual understanding of renal dysfunction results in re-consideration of principles of management of critically ill patients with special emphasis on factors that can cause (aggravate) kidney injury. The article focuses on the fact that the mechanistic implementation of any new techniques without regard to the consequences can bring not only benefits but also harm. It emphasizes that the prevention of the cohort of patients with chronic kidney disease from growing and adequate timely use of modern dialysis technologies can result in reduction of public spending on hemodialysis after discharge from the hospital. The effectiveness of interdisciplinary interaction of various professional communities jointly searching for solutions is illustrated by the example of the management of the antibiotic resistance problem.